Comprehensive evaluation of inactivated SARS-CoV-2 vaccination on sperm parameters and sex hormones - Dong, Yehao; Ba, Zaihua; Qin, Yining; Ma, Jiao; Li, Yuqi; Zhang, Yingze; Yang, Aijun; Chen, Fei (Frontiers in Immunology, 2024)
Background The inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine has made significant contributions to fighting the epidemic in the past three years. However, the rapid development and application raised concerns about its safety in reproductive health, especially after several studies had observed a decrease in semen parameters following two doses of mRNA SARS-CoV-2 vaccination. Thus, it is necessary to comprehensively evaluate the effect of inactivated SARS-CoV-2 vaccine on male fertility. Methods A retrospective cohort study was conducted in the Center for Reproductive Medicine of the Affiliated Hospital of Jining Medical University between July 2021 and March 2023. A total of 409 men with different vaccination status and no history of SARS-CoV-2 infection were included in this study. Their sex hormone levels and semen parameters were evaluated and compared separately. Results The levels of FSH and PRL in one-dose vaccinated group were higher than other groups, while there were no significant changes in other sex hormone levels between the control and inactivated SARS-CoV-2 vaccinated groups. Most semen parameters such as volume, sperm concentration, total sperm count, progressive motility and normal forms were similar before and after vaccination with any single dose or combination of doses (all P > 0.05). Nevertheless, the total motility was significantly decreased after receiving the 1 + 2 doses of vaccine compared to before vaccination (46.90 ± 2.40% vs. 58.62 ± 2.51%; P = 0.001). Fortunately, this parameter was still within the normal range. Conclusion Our study demonstrated that any single dose or different combined doses of inactivated SARS-CoV-2 vaccination was not detrimental to male fertility. This information could reassure men who want to conceive after vaccination and be incorporated into future fertility recommendations.